Pengaruh Celebrity Endorser, Citra Merek, Dan Kepercayaan Merek Terhadap Minat Beli Wardah Shampoo Sebagai Produk Perawatan Rambut Halal - Hasti Pramesti Kusnara; Haekal Pirous; Alpina Damayanti (CV. Ulil Albab Corp, 2026)
This study aims to analyze the influence of celebrity endorsers, brand image, and brand trust on purchase intention for Wardah Shampoo products amidst intense competition in the toiletries industry between global and local brands. Wardah, as the market leader in halal cosmetics, seeks to increase its market share in the hair care category by collaborating with Dewi Sandra as the brand representative. This research employs a quantitative approach using a survey method. The population consists of high school and university female students in the study area, with a sample of 287 respondents selected using stratified random sampling techniques. Data were collected via questionnaires and analyzed using Multiple Linear Regression with SPSS software. The results show that, both partially and simultaneously, celebrity endorser (Dewi Sandra), brand image, and brand trust have a positive and significant effect on purchase intention. The primary finding indicates that brand trust is the most dominant variable influencing consumer purchase intention. This implies that for this consumer segment, confidence in halal assurance and product effectiveness is more crucial than merely the popularity of the celebrity endorser to overcome brand inertia.